Application Research of Data Analysis and Mathematical Model Prediction in Marine Fishery. (August 2020) - Si, Yingqian; Huang, Ziling; Wu, Ruoxi
Abstract: Fishery resources are the biological resources which are constantly updated and changed, Global ocean temperature affects the habitat quality of some marine organisms. When the temperature changes too much to continue to live, these organisms begin to migrate to more suitable places. If fishery companies can understand the migration regular of fish when the ocean temperature changes in advance, it will improve the efficiency of fishing. On the basis of previous project research, this paper studies the influence of sea water temperature change on the migration of herring and mackerel in the North Atlantic of Scotland, and establishes a prediction model of sea temperature. The model predicts the temperature of the Western Ocean in different latitudes near Scotland in the next 50 years, so as to predict the migration direction and migration frequency of the two kinds of fish. Through time series regression analysis, the shortest, longest and average time for the two kinds of fish to leave Scotland were analyzed and the migration direction and frequency of these two species were predicted, which can provide a reference for small-scale fishery companies in the coastal area of Scotland to solve the problem of declining fishing rate due to migration of herring and Mackerel. The conclusion and method of this study can also provide reference for other similar cases.